The Epistle of Forgiveness : Volumes One and Two - Abū al-ʻAlāʼ al-Maʻarrī, 973-1057 (Book collections on Project MUSE., 2016)
Known as "one of the most complex and unusual texts in Arabic literature" (Banipal Magazine), The Epistle of Forgiveness is the lengthy reply by the prolific Syrian poet and prose writer, Abu l-'Ala' al-Ma'arri (d. 449 H/1057 AD), to a letter by an obscure grammarian, Ibn al-Qari. With biting irony, The Epistle of Forgiveness mocks Ibn al-Qari's hypocrisy and sycophancy by imagining he has died and arrived with some difficulty in Heaven, where he meets famous poets and philologists from the past. In al-Maarri's imaginative telling, Ibn al-Qari also glimpses Hell and converses with the Devil and various heretics.Al-Ma'arri--a maverick, a vegan, and often branded a heretic himself--seems to mock popular ideas about the Hereafter. Among other things, he introduces us to hypocrites, poets, princes, rebels, mystics, and apostates, with asides on piety, superstition, wine-drinking, old age, and other topics. This remarkable book is the first complete translation of this masterpiece into any language, all the more impressive because of Al-Ma'arri's highly ornate and difficult style, his use of rhymed prose, and his numerous obscure words and expressions. Replete with erudite commentary, amusing anecdotes, and sardonic wit, The Epistle of Forgiveness is an imaginative tour-de-force by one of the most pre-eminent figures in classical Arabic literature.